2023
DOI: 10.1038/s41598-023-31024-w
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome signatures of Yorkshire Terrier enteropathy during disease and remission

Abstract: The role of the gut microbiome in developing Inflammatory Bowel Disease (IBD) in humans and dogs has received attention in recent years. Evidence suggests that IBD is associated with alterations in gut microbial composition, but further research is needed in veterinary medicine. The impact of IBD treatment on the gut microbiome needs to be better understood, especially in a breed-specific form of IBD in Yorkshire Terriers known as Yorkshire Terrier Enteropathy (YTE). This study aimed to investigate the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Although the exact pathogenesis of IBD remains unclear, studies have suggested that alterations in the interaction between intestinal microbes and the mucosal immune system in susceptible individuals contribute to intestinal inflammation [78,79]. In dogs with specific IBD conditions, such as Yorkshire Terrier enteropathy and chronic canine IBD, reductions in the relative abundance of Alloprevotella, Phascolarctobacterium, Prevotellaceae, Oscillospirales, Oscillospiraceae UCG-005, Phascolarctobacterium, Succinivibrionaceae, and Succinivibrio have been observed [80,81]. Notably, the decreased abundance of Phascolarctobacterium has been associated with colon inflammation, regardless of the specific IBD phenotype [82].…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact pathogenesis of IBD remains unclear, studies have suggested that alterations in the interaction between intestinal microbes and the mucosal immune system in susceptible individuals contribute to intestinal inflammation [78,79]. In dogs with specific IBD conditions, such as Yorkshire Terrier enteropathy and chronic canine IBD, reductions in the relative abundance of Alloprevotella, Phascolarctobacterium, Prevotellaceae, Oscillospirales, Oscillospiraceae UCG-005, Phascolarctobacterium, Succinivibrionaceae, and Succinivibrio have been observed [80,81]. Notably, the decreased abundance of Phascolarctobacterium has been associated with colon inflammation, regardless of the specific IBD phenotype [82].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies related to IBD, where the subjects were the dogs that later served as IBD organoid donors in this study, we discovered that both the microbiome and metabolome experienced persistent disruptions even after the remission phase [ 46 , 47 , 48 ]. In the context of this study, the sustained perturbation of the microbiome and metabolome may suggest that IBD can lead to lasting alterations in the intestinal environment, necessitating more effective interventions such as stem cell therapy.…”
Section: Resultsmentioning
confidence: 97%
“…A variety of treatments are utilized, such as corticosteroids, fiber-enriched diets, and prebiotics, with no success in curing cIBD [1][2][3]. Underlying factors that contribute to GI disease include an animal's genetics, environmental factors, the immunological state of the GI tract and, importantly, an altered GI tract microbiome [4]. Microbial metabolism in the GI tract is important for the fermentation of various carbohydrates and the generation of short-chain fatty acids (SCFAs) that impact host health [5], such as by reducing intestinal inflammation [6].…”
Section: Introductionmentioning
confidence: 99%